A Case of Sphenoid Sinus Metastasis in Hepatocellular Carcinoma. Issue 6 (1st April 2016) - Lee, Tae Hoon; Rangan, Vikram; Khallafi, Hicham
Abstract : Sphenoid sinus metastasis from hepatocellular carcinoma (HCC) has been reported only rarely. We present a case of solitary sphenoid sinus metastasis of a 2.7 × 2.3 cm single HCC lesion. (Hepatology 2016;63:2050‐2053)